MODERN ASPECTS OF REHABILITATION OF WOMEN WITH POSTNATAL PERINEAL INJURIES - Kamarova Ibodat Nuriddinovna; Kamarova Muslima Nuriddinovna (Journals Park Publishing, 2022)
At present, every fifth birth in Uzbekistan is accompanied by soft tissue injuries in the birth tracts, the frequency of which has no tendency to decrease. The level of perineal dissection in labor remains high. Traditional methods of suture processing do not provide full healing. The results of the conducted researches testify that the inclusion of physiotherapy in the complex of preventive measures in the management of maternity hospitals with injuries of soft tissues of the birth canal helps to reduce infectious complications and provides a more favorable course of the postpartum period.
Keywords: labor traumatism, perineum, infectious complications